Respuesta :
Given the equation is 8+9z=-6, the first step would be to subtract the 8 from both sides:
8+9z-8=-6-8
Since 8 minus 8 = 0, this would cancel out the 8. And since -6 minus 8 equals -14, the equation would look like this
9z = -14
You move the constant to the right side and change its sign to be 9z= -6 -8. That’s the first step.
The second step would be calculate the difference of -8-6 to get -14. You equation should now be 9z=-14
The last step is to divide both sides by 9 to get z=-14/9
——————————————————————-
Hope this helps
The second step would be calculate the difference of -8-6 to get -14. You equation should now be 9z=-14
The last step is to divide both sides by 9 to get z=-14/9
——————————————————————-
Hope this helps